2016
DOI: 10.1017/s0022215116001031
|View full text |Cite
|
Sign up to set email alerts
|

Personal music systems and hearing

Abstract: These results suggest that listening to music through personal music systems at higher volume levels may be hazardous to hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
1
26
0
3
Order By: Relevance
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
“…The authors confirmed that four [9,[20][21][22] of the selected studies had "good" quality (scored 7-9). The remaining studies were evaluated as having "fair" quality (score 4-6) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] except for one study with a score of 3, evaluated as having "poor" quality [35]. Thus, 16 articles were included for systematic review and meta-analysis in this study.…”
Section: Selection Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The contention that personal music systems used at high volume are harmful to hearing is corroborated by Kumar and Deepashree's experimental work involving 60 participants. 4 The authors found that personal music systems used at high volumes led to: elevated high frequency thresholds, reduced frequency discrimination and temporal modulation detection, and poor speech perception. This puts in perspective university students' attitudes towards hearing loss caused by attendance at night clubs.…”
mentioning
confidence: 99%